2022
DOI: 10.7203/leeme.50.24657
|View full text |Cite
|
Sign up to set email alerts
|

¿Cómo se refleja la legislación educativa en los libros de texto? Un estudio de metodología mixta en relación a los contenidos mínimos de educación musical en el segundo ciclo (3-6 años) de educación infantil

Abstract: Si bien existen multitud de trabajos dedicados al estudio de la legislación educativa o de los libros de texto, son escasos los que se dedican a su investigación de forma conjunta. En el presente estudio, se ha investigado de qué manera la legislación estatal española que regula los contenidos mínimos preceptivos en Educación Infantil en la etapa de 3 a 6 años se refleja en los libros de texto, con respecto a los contenidos relativos al desarrollo de la educación musical. A través de una metodología mixta poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, Sungurtekin (2021) found that among the teachers participating in their study in Turkey, there was no significant emphasis placed on the creation of melodies, rhythms, or music composition. Moreover, Schiavio et al (2023) found that in fostering students’ creativity, their participants (who were based in Italy and Belgium) differentially highlighted “stimulating their curiosity,” “changing their perspectives,” and “helping them navigate both personal and social domains.” The limited research on conceptions about creativity in music education in the Spanish context underscores that its understanding is pre-scripted by educational regulations, based in traditional conceptions, and disregards creativity in listening (González-Ben, 2015; Mateos-Moreno & Gallego-García, 2022).…”
Section: Frameworkmentioning
confidence: 99%
“…However, Sungurtekin (2021) found that among the teachers participating in their study in Turkey, there was no significant emphasis placed on the creation of melodies, rhythms, or music composition. Moreover, Schiavio et al (2023) found that in fostering students’ creativity, their participants (who were based in Italy and Belgium) differentially highlighted “stimulating their curiosity,” “changing their perspectives,” and “helping them navigate both personal and social domains.” The limited research on conceptions about creativity in music education in the Spanish context underscores that its understanding is pre-scripted by educational regulations, based in traditional conceptions, and disregards creativity in listening (González-Ben, 2015; Mateos-Moreno & Gallego-García, 2022).…”
Section: Frameworkmentioning
confidence: 99%